Intensitas Perilaku Doomscrolling Siswa SMPN 2 Gurah: Mini Riset Konselor - Yulis khana; Henny Indreswari; Khairul Bariyyah (Universitas Majalengka, 2026)
The rise of social media has led to the phenomenon of doomscrolling, the habit of repeatedly browsing negative information, which can affect students’ psychological well-being. This study aimed to identify the intensity of doomscrolling behavior among students at SMPN 2 Gurah. The study employed a quantitative method using a Likert-scale questionnaire, distributed to 126 students in grades 7, 8, and 9. The results indicated that most students (approximately 75%) exhibited a high level of doomscrolling. These findings highlight the importance of the counselor’s role in raising students’ awareness of healthy social media use. This study provides an initial insight into doomscrolling behavior among adolescents and serves as a basis for developing more effective guidance strategies.